ENGENTASAN BUTA AKSARA TINGKAT DASAR MELALUI SEKOLAH KOLONG RUMAH DI KECAMATAN KELARA KABUPATEN JENEPONTO - Sapinah .,; Hariani Harjuna; Rusdianto .,; Andi Annisa Sulolipu (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2017)
In the world of education, community service activities such as basic illiteracy are currently needed, as illiteracy eradication is one of the world's problems, including in Indonesia, especially in Jeneponto district of South Sulawesi province. Where the number of illiterate population aged 15 years and over reached 9.65% of the 24 districts in southern Sulawesi at the same time ranks the 3rd largest number of people who bear illiteracy scattered in various regions in Jeneponto district.The method of implementation used in this devotion is: 1) the observation stage and the initial approach, 2) the extension and motivation stage, 3) Provide the facilities and infrastructure, 4) the basic level learning through the school under the house, 5) the provision of skills and 6) the evaluation stage .There is an increase in the knowledge of citizens from who could not write, know the letters and numbers to be able. The percentage of increasing the knowledge of the citizens on the study of letters in the village of Bontonompo is from 45.56% to 72.22% increase, while the percentage for the introduction of the figure is 51.11% increased to 81.11%. For the village Tombolo percentage for letter recognition is 56.67% to 88.89 while for the introduction of the number 63.33% increased to 87.78%. And for Gantarang village is 60% increased to 86.67 for learning letters and 54.44% increased to 81.11% for number recognition. Keyword:lliteracy, under the house, Jeneponto Regency